Predicting Depression Among Spouses of Ex-POWs: The Contribution of Exposure to Violence, Trauma, and Stress Through the Life Cycle - Hava, Dayan (Journal of interpersonal violence, 2023)
The current longitudinal study focused on predicting depression among spouses of former Israeli war veterans (combat veterans or ex-prisoners of war [ex-POWs]). The research examined the direct and moderating role of secondary trauma related to their husbands’ war-related experiences, stress related to being exposed to intimate partner violence in their relationship, being a second-generation Holocaust (SGH) survivor, and the effects of additional stressful life events (SLEs) since the end of the war. Wives of ex-POWs and combat veterans (N = 129) participated in two time measurements. Spouses of ex-POWs were found to be at higher risk of depression and psychological violence. Psychological violence was a risk factor for depression. The three-way interaction among psychological violence, being a SGH survivor, and experiencing SLEs was significant. In addition, experiencing earlier stressful events had a protective effect. The findings suggest that the association between early exposure and additive exposure through life is a complex iteration of factors and does not necessarily follow the vulnerability perspective.